Deployment of high-speed broadband in rural areas in the EU: Evolution of the investment gap and alternatives to reduce it - Jesús Ferrandis; Sergio Ramos; Claudio Feijóo (International Telecommunications Society (ITS), 2022)
This paper uses an estimation model to calculate the investment gap that needs to be covered to meet the objectives set by the European Commission in the context of the European Gigabit Society (EGS) regarding gigabit networks availability. It analyses the evolution of this gap between mid-2017 and mid-2019 and concludes that it will not be closed in the expected timeframe at the current pace of deployment, especially in rural areas, that are affected by higher costs to deploy. The paper also introduces a high-level assessment of different alternatives that have been proposed to ease the deployment of network and foresees alternative operating models as the most likely option to help reduce the gap in these rural areas.
Keywords: 330